Screening of Promising Maize Varieties Against Maize Weevil (Sitophilus zeamais Motschulky) Under Storage Condition - Sarjit Pandey; Dharma Raj Katuwal; Rashmi Aryal (Turkish Journal of Agriculture: Food Science and Technology)
The maize weevil (Sitophilus zeamais Motschulsky) causes significant quantitative and qualitative losses during storage. To identify resistant varieties of maize against this pest, an experiment was conducted in a Completely Randomized Design (CRD) with 11 varieties in free and no-choice conditions. The study measured weight loss, mean bored grain, debris, and weevil numbers at 30, 60, and 90 days. The findings showed that BG13Y-POP, Manakamana-7, and RML-19/RML-6 were the most resistant varieties, with weight loss percentages of 1.99%, 1.47%, and 1.74%, respectively, and final weevil numbers of 104, 72, and 73. Ganesh-2 and ZM-401 were the most susceptible varieties, with weight losses of 7.34% and 6.05%, respectively. The maximum debris weight was found in RML-761/RL-105 (1.98 g), while the minimum was found in Manakamana-7 (0.26 g). The highest number of bored grains was observed in Ganesh-2 (81), while the lowest number was observed in Rampur-4 (51). Similarly, ZM-401 (158) and Ganesh-2 (165) exhibited the highest weevil population, while the lowest count was found in Rampur-4 (72). Overall, using resistant varieties, such as Manakamana-7, BG13Y-POP, and RML-19/RML-6, can be an effective approach for reducing post-harvest losses from weevil infestation.